The Influence of Visionary Leadership and Persuasive Communication on Teacher Performance in Schools - Sabariah, Sabariah; Akbar, Nadzmi; Sulistiami, Sulistiami; Qatrunida, Qatrunida; Rahmadi, Rahmadi (JURNAL AL-TANZIM, 2023)
This paper discusses the influence of visionary leadership and persuasive communication on teacher performance at the Global Islamic Boarding School, South Kalimantan. Teacher performance is an essential component and needs special attention, considering that teacher performance significantly impacts student learning outcomes. This research uses a quantitative approach, and the sample was taken using a non-probability sampling technique with 40 respondents. The research results show that The t-count value for the visionary leadership variable of 2,764 is greater than the t-table of 2.02439 with a significance level of 0.009 < 0.05. This shows that visionary leadership has a positive effect on teacher performance. (2) The results of data analysis show that the t-count value is 1.203 < t-table 2.02439, with a significant value of 0.237 > 0.05. This states that Ha is rejected and Ho is accepted, meaning that the persuasive communication variable does not positively and significantly affect the teacher performance variable. (3) Based on the results of the F-test, it shows that the F-value is 4,590 > from F table 0.25, and the significant value is 0.018 < 0 .05; this shows that visionary leadership and persuasive communication have a simultaneous effect on teacher performance.